A review on selection criteria of aqueous electrolytes performance evaluation for advanced asymmetric supercapacitors. (August 2021) - Sajjad, Muhammad; Khan, Muhammad Ibrar; Cheng, Fang; Lu, Wen
Highlights: The effect of different parameters on the properties of aqueous electrolytes has been overviewed in a details in this review paper. The basic building blocks that determine of aqueous electrolyte are outlined. The problems, challenges, and future research direction is proposed for further advancements in aqueous electrolytes. Aqueous electrolytes used for aqueous asymmetric supercapacitors and their performance is summarized in a great details in this review paper. Abstract: Aqueous asymmetric supercapacitors (AASCs) are a leading candidate for energy storage systems due to their low cost, high energy and power densities, and excellent cyclic stability. Unfortunately, owing to the H2 /O2 potential range at 1 atm at room temperature, aqueous electrolytes have a short potential window (1–1.23 V). Energy density, in addition to the supercapacitor's advantageous position in an electrolyte solution, is used to evaluate other critical parameters such as rate performance, equivalent series resistance, power density, operating temperature range, cyclability, toxicity, and self-discharge rates, all of which are important in real-world applications. This review article looks at the most recent developments in aqueous electrolyte research and processing, as well as the impact of electrolyte properties on supercapacitor performance. The interaction of the materials with electrolytes, other electro-active materials, and inactive components are analyzed to understand their effects on the performance of supercapacitors. The ionic conductivity, mobility, diffusion coefficient, the radius of bare and hydrated spheres, ion solvation, viscosity, dielectric constant, electrochemical stability, thermal stability, solvent interaction, and techniques like nano-structuring and hybridization, are systematically discussed for improving electrode performance in this review paper. Finally, outstanding challenges and possible solutions about the complexities and problems of dealing with aqueous electrolytes are briefly presented with some perspectives toward the future development. Many feasible research paths are suggested to address these issues in future efforts to increase the energy efficiency of AASCs without sacrificing their current benefits.